740 Insomnia, cognitive arousal, and perinatal-focused rumination fuel perinatal depression. (3rd May 2021) - Castelan, Andrea Cuamatzi; Kalmbach, David; Cheng, Philip; Drake, Christopher
Abstract: Introduction: Depression is among the most prevalent perinatal complications, yet modifiable risk factors remain elusive. Over half of perinatal women endorse clinical insomnia symptoms, which are etiologically implicated in depression in non-perinatal samples. Yet, prospective data on perinatal insomnia and depression are mixed. We sought to clarify temporal associations of insomnia and depression during peripartum, and to investigate cognitive arousal as a potential mechanism facilitating this relationship. Methods: Seventy pregnant women completed sociodemographic information and baseline sleep and mood symptoms between gestational weeks 25–30. Beginning at gestational week 30, participants completed 17 weekly online surveys assessing insomnia, depression, and three cognitive arousal indices (nocturnal cognitive arousal, perseverative thinking, perinatal-focused rumination). Mixed effects models were conducted to test hypotheses. Results: Women were at elevated risk of screening positive for depression when experiencing high levels of insomnia (OR=2.36, 95%CI=1.28, 4.35), nocturnal cognitive arousal (OR=3.05, 95%CI=1.60, 5.79), perinatal-focused rumination (OR=2.05, 95%CI=1.11, 3.79), and perseverative thinking (OR=7.48, 95%CI=3.90, 14.32). Prospective analyses revealed bidirectional effects between insomnia and cognitive arousal, and both predicted future depression. Nocturnal cognitive arousal mediated 23–43% of the effect of insomnia on depression. Insomnia mediated 12–18% of the effect of nocturnal cognitive arousal on depression. A similar pattern was observed with perinatal-focused rumination. Depression did not predict insomnia. Conclusion: Perseverating at night, particularly on perinatal concerns, fuels insomnia. In turn, lying awake at night provides ample opportunity for perseverating. This cycle feeds perinatal depression. Daytime cognitive arousal may indirectly disrupt sleep as perseverating during the day persists into the night. Support (if any):